Mathematical Analysis in Static Equilibrium of Economics: as Support to Microeconomics Course - Upadhyaya, Yadav Mani (Interdisciplinary Journal of Management and Social Sciences, 2020)
Microeconomics studies the economic behavior of individual decision-makers. To be able to make sound decisions in economics, the economist has designed mathematical models based on the differentiation of simple functions. Economics and mathematics are directly related as changes in quantities and variables affect the relationship and the direction of the consumer behavior to become better –off or worse-off. The main objectives of this study are microeconomic theories that may simplify or easily understandable through the mathematical calculation to illustrate the examples and calculate the equilibrium positions numerically. The study also aims to provide mathematical tools that manage to determine all the information necessary for decision making from a broad vision. The relationship between quantity and price may be better explained through mathematical notations. The supply and demand curve is designed to find the equilibrium point and it is better explained through mathematical equations. To explain, the methodology is used for a simple mathematical function of price with the help of a simple linear and nonlinear model of static analysis of the market equilibrium of Qd=Qs. This study concludes that it will greatly help college students, professionals, entrepreneurs, and in general anyone presents solved exercise and proposes problems, for the student to solve cases create graphs, table, and interpret and analyze results in the market and thus fixing the knowledge.